The interaction and binding of flavonoids to human serum albumin modify its conformation, stability and resistance against aggregation and oxidative injuries - Barreca, Davide; Laganà, Giuseppina; Toscano, Giovanni; Calandra, Pietro; Kiselev, Mikhail A.; Lombardo, Domenico; Bellocco, Ersilia (Biochimica et biophysica acta. General subjects, 2017)
Interactions of ligands with proteins imply changes in the properties of the macromolecules that may deeply modify their biological activities and conformations and allow them to acquire new and, sometimes, unexpected abilities. The flavonoid phloretin has several pharmacological properties that are starting to be elucidated, one of which is the well-known inhibition of glucose transport. The interactions of phloretin to human serum albumin have been investigated by fluorescence, UV–visible, FTIR spectroscopy, native electrophoresis, protein ligand docking studies, fluorescence and scanning electron microscopy. Spectroscopic investigations suggest that the flavonoid binds to human serum albumin inducing a decrease in α-helix structures as shown by deconvolution of FTIR Amide I′ band. Fluorescence and displacement studies highlight modifications of environment around Trp214 with the primary binding site located in the Sudlow's site I. In the hydrophobic cavity of subdomain IIA, molecular modeling studies suggest that phloretin is in non-planar conformation and hydrogen-bonded with Ser202 and Ser454. These changes make HSA able to withstand protein degradation due to HCLO and fibrillation. Our work aims to open new perspectives as far as the binding of flavonoids to HSA are concern and shows as the properties of both compounds can be remarkable modified after the complex formation, resulting, for instance, in a protein structure much more resistant to oxidation and fibrillation. This article is part of a Special Issue entitled “Science for Life” Guest Editor: Dr. Austen Angell, Dr. Salvatore Magazù and Dr. Federica Migliardo. [Display omitted] •Phloretin–HSA complex formation involves property changes in both compounds.•Phloretin binds to protein in subdomain IIA.•Phloretin modifies the secondary structure of HSA•Phloretin–HSA complex is able to withstand degradation due to HCLO and fibrillation.